2011
DOI: 10.1159/000324101
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Aneuploidization during the Expansion of Renal Adenocarcinoma

Abstract: Background/Aims: A correlation has been observed between DNA ploidy and other prognostic parameters such as tumor stage and grade. The present study evaluates tumor aneuploidization during renal adenocarcinoma expansion and growth. Methods: A total of 252 renal tumors were analyzed between 1969 and 2001. Evaluated variables were age, TNM, Fuhrman classification, histology, size and DNA. A tumor was homogeneous when all the samples were diploid or aneuploid, and a heterogeneous tumor was the coexistence of aneu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…To accomplish this, we took advantage of naturally occurring Robertsonian translocations to generate mouse embryonic fibroblasts (MEFs) trisomic for chromosome 1, 13, 16, or 19, as well as sibling-matched euploid controls (Williams et al, 2008). While advanced malignancies frequently harbor complex karyotypes that include multiple chromosome gains and/or losses, early-stage cancers typically exhibit one or a few arm-length or whole-chromosome aneuploidies (Balaban et al, 1986; Di Capua Sacoto et al, 2011; Lai et al, 2007; Magnani et al, 1994; El-Rifai et al, 2000). Thus, these trisomies likely recapitulate the karyotypic state of pre-malignant or early-stage cancer lesions, and their study can shed light on the role of aneuploidy in cancer development and evolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To accomplish this, we took advantage of naturally occurring Robertsonian translocations to generate mouse embryonic fibroblasts (MEFs) trisomic for chromosome 1, 13, 16, or 19, as well as sibling-matched euploid controls (Williams et al, 2008). While advanced malignancies frequently harbor complex karyotypes that include multiple chromosome gains and/or losses, early-stage cancers typically exhibit one or a few arm-length or whole-chromosome aneuploidies (Balaban et al, 1986; Di Capua Sacoto et al, 2011; Lai et al, 2007; Magnani et al, 1994; El-Rifai et al, 2000). Thus, these trisomies likely recapitulate the karyotypic state of pre-malignant or early-stage cancer lesions, and their study can shed light on the role of aneuploidy in cancer development and evolution.…”
Section: Resultsmentioning
confidence: 99%
“…First, our study has primarily focused upon the consequences of single-chromosome trisomies and tetrasomies. This degree of aneuploidy is frequently observed in early-stage lesions in a variety of tumor types (Balaban et al, 1986; Di Capua Sacoto et al, 2011; Lai et al, 2007; Magnani et al, 1994; El-Rifai et al, 2000). It could be the case that these low levels of aneuploidy are in fact tumor protective, while complex karyotypes or the multiple chromosome gains found in more advanced malignancies are tumor promoting.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have demonstrated similar results regarding the independent prognostic value of DNA ploidy for survival and tumor progression [12,13] .…”
Section: Discussionmentioning
confidence: 61%
“…Fuhrman et al [11] have demonstrated that nuclear grade is better than other prognostic variables in predicting the development of metastasis after nephrectomy in RA. However, in many studies (including this study), nuclear grade achieved independent prognostic value for survival only when grouped in two or three categories [12][13][14] . Only a few studies with larger sample sizes have demonstrated the prognostic value of the nuclear grade when considering its four categories [15,16] .…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation